FAKTOR PENYEBAB PERCERAIAN DINI DI KOTA TASIKMALAYA - Nurhayati, Nunung; Sholihah, Hani (Institut Nahdlatul Ulama Tasikmalaya, 2025)
This article explores the underlying factors contributing to early divorce in the city of Tasikmalaya, with a specific focus on couples who ended their marriages within the first five years. The aim of this study is to identify and analyze the main triggers of early divorce based on the perspectives of individuals who have directly experienced it. The research employs a qualitative method through in-depth interviews with three participants who went through early divorce. In addition, a literature review of academic and religious references supports the findings. The results indicate that early divorce is generally caused by couples’ unpreparedness in facing the challenges of married life, a lack of understanding regarding marital roles and responsibilities, poor communication, and financial pressures. A significant factor is the absence of sufficient knowledge, emotional maturity, and readiness prior to marriage, which increases the vulnerability to conflicts in the early years of marriage. This issue is often exacerbated by societal tendencies to prioritize the ceremonial aspects of weddings over the substantive preparation for family life. While Islam permits divorce under certain conditions, it remains an act that is disliked by Allah SWT. Therefore, to prevent early divorce, it is crucial to strengthen the foundations of marriage through comprehensive premarital education—emotionally, spiritually, and financially—in order to build a harmonious and resilient family characterized by sakinah, mawaddah, and rahmah.